Open‐Label, Phase II Study to Assess the Efficacy and Safety of Canakinumab Treatment in Active Hyperimmunoglobulinemia D With Periodic Fever Syndrome. Issue 8 (5th July 2017) - Arostegui, Juan I.; Anton, Jordi; Calvo, Inmaculada; Robles, Angel; Iglesias, Estibaliz; López‐Montesinos, Berta; Banchereau, Romain; Hong, Seunghee; Joubert, Yolandi; Junge, Guido; Pascual, Virginia; Yagüe, Jordi
Abstract : Objective: To evaluate the efficacy and safety of canakinumab treatment in active hyperimmunoglobulinemia D with periodic fever syndrome (HIDS). Methods: This was a 3‐part open‐label study with an initial 6‐month treatment period in which patients with HIDS (n = 9) received canakinumab subcutaneously at a dose of 300 mg (or 4 mg/kg for those weighing ≤40 kg) every 6 weeks (period 1 [P1]), followed by a 6‐month withdrawal period (period 2 [P2]), and then a 24‐month extension treatment period with canakinumab at the same dose (period 3 [P3]). The primary end point was reduction in the frequency of attacks during treatment periods as compared to the historical period (HP; defined as the period in which patients did not receive drugs other than nonsteroidal antiinflammatory drugs and/or steroids). Results: All 9 patients completed P1 and P2, whereas only 8 patients completed P3. All patients achieved a complete response during P1, and only 2 required dose adjustments. The number of attacks per patient decreased from a median of 5 (range 3–12) during the HP to a median of 0 (range 0–2) during P1. During P2, 7 of 9 patients experienced a disease flare within a median of 110 days (range 62–196) after the last canakinumab dose. Laboratory findings were normalized by day 15 of treatment and remained at normal levels throughout the study. Analysis of blood transcriptome profiles, assessed during P1, showed up‐regulated levels of interferon and myeloid‐related inflammatory responses in untreated patients compared to healthy controls, and these rapidly decreased following canakinumab injection, reaching levels comparable to those of healthy controls. At least 1 adverse event (AE) was detected in all 9 patients. Most of the AEs were mild in intensity, with infections being the most frequent AE. Serious AEs were reported in 4 patients. Conclusion: The results of this study demonstrate the efficacy and safety of canakinumab treatment to control active HIDS and to suppress inflammation‐related transcriptional responses.